A changing role in global climate governance: São Paulo mixing its climate and international policies (2019)
Cities have been playing an important role in global climate governance for the last two decades, providing climate responses such as mitigation and adaptation policies. The city of São Paulo has positioned itself as one of the “new leaders” combining climate responses with an active international strategy. We analyze the role of São Paulo in global climate governance by crossing its climate and its international agendas from 2005 to 2018. The results demonstrate that São Paulo performed a leadership role during the phase of designing and adopting climate responses, but failed to sustain this position during the implementation phase. © 2019, INSTBRASILEIRORELACOESINT. All rights reserved.